Pathogenicity assay and molecular identification of fungi and bacteria associated with diseases of tomato in Malaysia - Rashid, Tavga Sulaiman; Sijam, Kamaruzaman; Awla, Hayman Kakakhan; Mohd Saud, Halimi; Kadir, Jugah (Scientific Research Publishing, 2016)
This study was conducted in order to determine the fungi and bacteria associated with tomato plants at Cameron Highlands Malaysia. The fungi which have been isolated and detected from tomato plants were: Fusarium oxysporum, F. solani, F. acuminatum, Rhizoctonia solani, Colletotrichum boninense, C. acutatum and Phoma destructiva. The bacteria which have been isolated and detected from tomato plants were: Ralstonia solanacearum, Xanthomonas vesicatoria, X. gardneri and Pseudomonas syringae. While the most pathogenic fungi were C. boninense, P. destructive and F. oxysporum with the disease incidence (89.6%, 86.6%, 85.6%) respectively, the most pathogenic bacteria were X. vesicatoria and R. solanacearum with the disease incidence (96.6% and 87.6%) respectively.